Meningkatkan Kemampuan Motorik dan Kognitif melalui Permainan Board Game pada Lansia di Panti Sosial Tresna Werdha Jayapura - Lusye Howay; Venthy Angelika; Inda Puspita Sari; Dwi Angriyani (Universitas Muhammadiyah Manado, 2025)
Growing life expectancy continues to shift global demographic patterns and significantly increase the proportion of older adults, thereby creating an urgent need for innovative programs that promote wellbeing, maintain functional capacity, and encourage meaningful social participation. This community service initiative aimed to strengthen both motor and cognitive function among older adults through structured and interactive board game activities designed to stimulate thinking, coordination, and social interaction. The program employed a mixed descriptive approach, utilizing interviews, direct observation, and brief assessments conducted before and after the intervention period. Cognitive status was measured using the Mini Mental State Examination (MMSE), while muscle strength was assessed through Manual Muscle Testing (MMT) to capture changes in physical performance. Quantitative analysis revealed no statistically significant differences between pre-test and post-test scores (p > 0.05). Nevertheless, qualitative findings demonstrated meaningful positive changes, including increased motivation, more active participation, improved emotional responsiveness, enhanced social interaction, and greater awareness of brain–body coordination among participants. These findings indicate that although short-term measurable changes were limited, board game–based activities can provide valuable psychosocial benefits. When implemented repeatedly and consistently as part of routine programs, such activities may contribute to maintaining cognitive engagement, supporting emotional wellbeing, and fostering a more active and participatory lifestyle among older adults.